(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Probiotic quail farming is a business that has good prospects in the Bandung area. This is because the demand for quail meat and eggs tends to increase from year to year, along with the increasing population growth and the increasing number of people who are aware of healthy living. The increasing demand for quail meat and eggs indicates that business opportunities in the field of quail breeding are still wide open. Therefore, it is necessary to analyze whether the business is feasible to run or even vice versa. This study examines opportunities for quail business development based on entrepreneurial aspects and aspects of business feasibility studies consisting of legal aspects, market and marketing aspects, technical and technological aspects, and management and human resources aspects. The results of the study show that investment in the development of probiotic quail businesses in Bandung is seen from the legal aspect, this business is more appropriate to use a form of individual business. The market aspect and marketing are very marketable, while the management aspects and human resources needed are widely available. These results indicate that the development of probiotic quail business is feasible because it can provide benefits.